Construction of financial constraint index, and the impact of financial constraint on firms’ cash holding and investment behavior: Evidence from UK manufacturing industry - LIU, FENGYUAN (2016)
This paper aims to construct a unique index of financial constraint for UK market and use the index to investigate the influence of financial constraint on UK firms’ cash holding and investment behavior. As for this purposes, all manufacturing listed firms’ data in UK during 2007 to 2015 are collected as the sample. By constructing the index, I found that the cash flow, cash ratio, leverage, and age are the key factors to explain the financial constraint. Moreover, by using the index into the further liquidity demand and investment demand model, I found that constrained firms have higher cash level and cash flow sensitivity of cash compared to unconstrained firms, and they have lower investment level and cash flow sensitivity of investment than unconstrained firms.